2005
DOI: 10.1080/14765280500040518
|View full text |Cite
|
Sign up to set email alerts
|

Stock return volatility and trading volume: evidence from the chinese stock market

Abstract: This study investigates the dynamic relationship between stock return volatility and trading volume for individual stocks listed on the Chinese stock market as well as market portfolios of these stocks. We found that the inclusion of trading volume, which is used as a proxy of information arrival, in the GARCH specification reduces the persistence of the conditional variance dramatically, and the volume effect is positive and statistically significant in all the cases for individual stocks. Consistent with our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…If we accept the criterion widely used in previous studies, this result indicates that volume may explain ARCH effects in the context of individual equity level but not at the market-wide index level. This result is in some way consistent with Wang, Wang, and Liu's (2005) finding, which suggests that information arrivals represented by trading volume tend to be company specific. However, we have a different assumption for our finding from that which Wang, Wang, and Liu (2005) make.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…If we accept the criterion widely used in previous studies, this result indicates that volume may explain ARCH effects in the context of individual equity level but not at the market-wide index level. This result is in some way consistent with Wang, Wang, and Liu's (2005) finding, which suggests that information arrivals represented by trading volume tend to be company specific. However, we have a different assumption for our finding from that which Wang, Wang, and Liu (2005) make.…”
supporting
confidence: 92%
“…In the literature, the conclusions of Lamoureux and Lastrapes (1990) and Wang, Wang, and Liu (2005) are drawn from the dramatically subsumes in their estimated and values. However, this simple inference method turns out to be problematic, which is later criticised by Omran and McKenzie (2000), Wagner and Marsh (2005) and Ostdiek (2006, 2008).…”
Section: Estimation Results For the Benchmark Volatility Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies mainly return to (Rogalski, 1978), (Figlewski, 1981), and (Cornell, 1981), these studies sought to examine the relationship between these variables, which found that there is a positive relationship between risk, trading volume, and stock return. Also (Wang et al, 2005) tested the relationship between the behavior of market stock returns, volatility of returns (Risk), and trading volume. The results confirmed that the volume of trading , which was used as a measure of information access, has a positive effect on the stock return.…”
Section: Introductionmentioning
confidence: 99%